The Eidi bag - Afzal, Shazia (Owlkids Books, 2025)
"Sarah is excited to celebrate Eid al-Fitr in her new country. Her mother warns her that things might be different than they were in Pakistan, but that doesn't faze her one bit. She has her Eidi bag ready and expects to receive enough gifts of money from friends and family for new markers and treats for her friends. But when Sarah arrives at the masjid, no one pays any attention to her waiting Eidi bag -- not Sana Khala, not Uncle Hamza, and not even Sister Salma! In Pakistan, her bag would be filled with money and she'd be able to buy goodies and toys. But instead she heads home from prayer feeling sad and disappointed -- and wishing that she'd never left Pakistan. Then, later that day, as friends and family begin to arrive at her house to celebrate Eid, they bring gifts that give Sarah a new perspective and appreciation for the traditions of her adopted country."--